2012
DOI: 10.1016/j.jpeds.2012.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Anemia, Apnea of Prematurity, and Blood Transfusions

Abstract: Objective To compare the frequency and severity of apneic events in very low birth weight (VLBW) infants before and after blood transfusions using continuous electronic waveform analysis. Study design We continuously collected waveform, heart rate, and oxygen saturation data from patients in all 45 neonatal intensive care unit beds at the University of Virginia for 120 weeks. Central apneas were detected using continuous computer processing of chest impedance, electrocardiographic, and oximetry signals. Apne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 16 publications
0
36
1
1
Order By: Relevance
“…25,26 A recent study that used a novel computer algorithm to detect apnea, bradycardia, and oxygen desaturation in continuously recorded physiologic data from 67 preterm infants showed decreased apnea for the 3 days after blood transfusions compared with 3 days before. 27 These authors also reported that the probability of an apnea event in a 12-hour epoch was higher with a lower hematocrit, adjusted for PMA. These results suggest that anemia may increase the likelihood of apnea of prematurity and that blood transfusions may result in a short-term reduction in apnea.…”
Section: Blood Transfusionmentioning
confidence: 94%
“…25,26 A recent study that used a novel computer algorithm to detect apnea, bradycardia, and oxygen desaturation in continuously recorded physiologic data from 67 preterm infants showed decreased apnea for the 3 days after blood transfusions compared with 3 days before. 27 These authors also reported that the probability of an apnea event in a 12-hour epoch was higher with a lower hematocrit, adjusted for PMA. These results suggest that anemia may increase the likelihood of apnea of prematurity and that blood transfusions may result in a short-term reduction in apnea.…”
Section: Blood Transfusionmentioning
confidence: 94%
“…The likelihood of having apnea in the 12 hours following transfusion was related to hematocrit. 54 Despite not being able to consider red blood cell transfusion as a treatment for moderately anemic infants with AOP, this option should be evaluated on a case by case basis.…”
Section: Red Blood Cell Transfusionmentioning
confidence: 99%
“…When indicated, transfusions decrease apnea of prematurity [40,41], may decrease neurologic adverse effects [42], and improved cerebral oxygen delivery, which may improve neuro developmental outcome [43]. DCC may also decrease the need for neonatal transfusions.…”
Section: Preterm Neonatesmentioning
confidence: 99%